On the (non) distinctiveness of Marxism-Leninism: The Portuguese and Greek communist parties compared. Issue 2 (June 2016) - Keith, Dan; Charalambous, Giorgos
Abstract: The study of parties that label themselves as Marxist-Leninist has, for the most part been subsumed in the exploration of the broader radical (or, far) left tradition in the post-1989 period. In an attempt to bridge this gap in the recent literature on radical left parties, this article attempts to uncover the (non) distinctiveness of Marxism-Leninism by studying empirically two European parties that are self-labelled as Marxist-Leninist – the Greek (KKE) and Portuguese (PCP) Communist parties. The central question we explore is whether there are significant similarities between these parties, so as to allow us to speak of Marxism-Leninism's distinctiveness today. Overall, the two parties studied here have enough in common to testify to Marxism-Leninism's ongoing distinctiveness with several qualifications, especially concerning ideology.